Riachos em condição de referência em uma bacia neotropical: variação natural do habitat físico e sua influência sobre a estruturação da ictiofauna - Caldeira, Yuri Malta (2016)
Reference condition areas are ecosystems in which the biotic and abiotic relationships are most similar to their natural conditions in the absence of human interference. The physical and biotic characterization of reference condition areas sets essential standards for assessment, management, and recovery of ecosystems. Despite being a well-developed subject in temperate countries, the study of reference condition areas for freshwater ecosystems is incipient in the tropical region which ironically holds a great part of freshwater biodiversity. The lack of knowledge on reference conditions is especially alarming for developing tropical countries such as Brazil where there is a large impact of the primary sector of the economy on freshwater ecosystems. Thus, we assessed the physical habitat conditions and the ichthyofaunal composition of 31 reference condition streams in the São Francisco river baisn, in the Brazilian state of Minas Gerais, in order to understand the natural spatial variation of the physical habitat and its relationship with the structuring of fish assemblages in a Neotropical river basin. We sampled 255 physical habitat metrics in each stream and a total of 4297 fishes of 50 different species was registered. The natural physical habitat conditions of the streams depended on their geographic position: streams located near to each other had more similar conditions. Mean elevation and water flow were positively related to the natural condition of substrate, fish shelter and riparian vegetation, and water chemistry and channel morphology of streams in a same region, respectively. Additionally, most (51%) of the natural variation of the composition of fish assemblages was explained by the geographic position (27%), frequency of riffles (14%), flow heterogeneity (6%), and abundance of woody fish shelter (5%) of reference condition streams. The relevance of geographic position for the explanation of the natural variation of physical habitat conditions and compositions of fish assemblages reflects the influence of landscape characteristics on streams. It also indicates that regional rather than basin-sclae reference conditions are more appropriate for the São Francisco river basin. Furthermore, we observed that local physical habitat characteristics related morphological adaptations of fishes are equally important as landscape chracteristics for the structuring of fish assemblages of sterams. The present results are the first contribution to the study of reference condition streams in a Neotropical river basin. They indicate the necessity of acting at different spatial scales to promote better conservation strategies for Neotropical freshwater ecosystems.